Are acceleration and cardiovascular capacities related to perceived load in professional soccer players?. Issue 1 (2nd January 2020) - Azcárate, Unai; Los Arcos, Asier; Jiménez-Reyes, Pedro; Yanci, Javier
ABSTRACT: This study aims at assessing physical fitness performance and its relationship with the differential ratings of perceived exertion of training load (dRPE TL) and match load ( dRPE ML) in a Spanish professional soccer team at the beginning of several in-season periods: 1–4 weeks, 5–8 weeks and 1–8 weeks. Performance and mechanical variables over the acceleration phase, as well as cardiovascular performance variables were evaluated in 20 male professional soccer players of a team competing in the Spanish Second Division League. Moreover, dRPE TL and dRPE ML were quantified. The dRPE TL showed negative and large associations between both maximal aerobic speed (MAS) and maximal oxygen consumption (VO2max ) (from r = −0.53; ± 0.06 to r = −0.53; ± 0.05 95% CL, p = 0.035 to 0.036 ) and RPEres TL values throughout the 5–8 and 1–8 week periods. Furthermore, dRPE ML positive and large associations were found between players initial MAS or VO2max (from r = 0.50; ± 0.17 to r = 0.56; ± 0.11 95% CL, p = 0.026 to 0.049 ) and RPEmus ML in 1–4 and 1–8 week periods. The current study suggests that a better cardiovascular capacity could be connected with a lower RPEres TL and higher RPEmus ML.